Pengaruh Latihan Static Stretching terhadap Penurunan Nyeri Otot Leher pada Petani Kakao di Desa Candikusuma Kecamatan Melaya - A.A. Ayu Alit Sitawati; Ns Ni Rai Sintya Agustini; Ns Dwi Prima Hanis Kusumaningtiyas (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Introduction: Cocoa farmers are prone to experiencing neck muscle pain due to repetitive physical activities with prolonged duration. Neck muscle pain can reduce productivity and quality of life. This study aimed to analyze the effect of static stretching exercises on reducing neck muscle pain among cocoa farmers in Candikusuma Village. Methods: This research used a pre-experimental design with a pre-test and post-test approach. The sampling technique was consecutive sampling with a total of 62 respondents. The static stretching exercise intervention was conducted for 1 week with a frequency of 2 sessions and a duration of 30 minutes per session. The research instrument used the Numeric Rating Scale (NRS). Results: Data were analyzed using the Wilcoxon Signed Rank Test, resulting in a p-value of 0.001 (p<0.05), indicating a significant effect of static stretching exercises on reducing neck muscle pain among cocoa farmers. Discussion: Static stretching exercises can be recommended as a non-pharmacological therapy to reduce neck muscle pain in the cocoa farmer population.